Islamic Jurisprudence Rules Dynamics in Justifying, Correcting and Completing Banking Transactions - Seyyed Alimohammad yasrebi (پژوهش‌های فقهی مسائل مستحدثه)
This article examines the application of Islamic jurisprudential rules in the context of Islamic banking, employing a moderate approach grounded in practical experience and investigation. The article explores various topics, including the rules of "Kul Qardh Jarr Manfa’ah Fahuwa Riba"[1], "Sihat"[2], "Akal Māl bi Bātil"[3], "Maqbūdh bi Aqd Fāsid"[4], "Nafy-e Qharar"[5], "Al-Uqūd Tābi’ah lil-Qusūd"[6], "Al-Muminūn Ind Shurūtihim"[7], and "Istīmān"[8] with deference to their implications in banking contracts, banking transactions and regulations of non-usurious banking operations. Recruiting a descriptive-analytical approach, the article delves more exclusively into the status of these rules in banking civil partnership and Mudhāribah[9] contracts. [1] the prohibition of the interest included in a loan as dirty money.[2] principle of validity of transactions.[3] Acquisition of a property using dishonest techniques.[4] Property acquired through a corrupt contract because the conditions for the validity of the contract were blatantly disregarded.[5] The prohibition of fraudulent transactions, especially where the seller is aware of the fraud.[6] According to this rule, the element of intention is an essential component in transaction contracts.[7] According to this rule, it is obligatory that Muslims remain faithful to their promises in a transaction contract.[8] According to this rule, the individual is liable to the damages inflicted on the property he is entrusted with.[9] It’s a kind of contract where the profit is divided between the contractor and the investor.Yasrebi, S.A.M. (2023) Dynamics of Islamic Jurisprudential Rules in the Justification, Modification, and Completion of Banking Transactions. Journal of New Perspectives in Islamic Jurisprudence, 1 (1) 1-15. Doi: https://doi.org/10.22091/RCJL.2023.9858.1027.